Role of Long Non-Coding RNA GUSBP11 in Chronic Periodontitis Through Regulation of miR-185-5p: A Retrospective Cohort Study - Zhang X; Shen X (Journal of Inflammation Research)
Xiaowen Zhang, Xiang Shen Department of Stomatology, Affiliated Hospital of Nantong University, Nantong, Jiangsu, 226001, People’s Republic of ChinaCorrespondence: Xiang Shen, Department of Stomatology, Affiliated Hospital of Nantong University, No. 20, Xisi Road, Chongchuan District, Nantong, Jiangsu, 226001, People’s Republic of China, Tel +86-0513-81161901, Email Shenxiangdr@163.comPurpose: Previous studies have shown that long non-coding RNA GUSBP11 is abnormally expressed in patients with periodontitis, but the specific mechanism remains to be investigated. The purpose of this study was to explore the role of GUSBP11/miR-185-5p in chronic periodontitis (CP) and its potential mechanism, so as to provide a basis for elucidating the pathogenesis of CP.Patients and Methods: The expression trends of GUSBP11 and miR-185-5p in gingival crevicular fluid of CP patients and control group were analyzed by RT-qPCR. Human gingival fibroblasts (HGF) induced by 10μg/mL LPS were used to construct CP cell models in vitro. The level of intracellular gene expression is regulated by cell transfection. The cell viability of HGF was evaluated by CCK-8 method, and the expression of HGF inflammatory factors was evaluated by ELISA. The targeting relationship between GUSBP11 and miR-185-5p was confirmed by luciferase reporter gene. The target genes of miR-185-5p were predicted using an online database, and the intersection target genes were obtained by constructing Venn diagram. Then GO analysis and KEGG pathway enrichment analysis were performed.Results: Compared with the control group, the expression levels of GUSBP11 and miR-185-5p in gingival crevicular fluid of CP patients were up-regulated and down-regulated, respectively (P < 0.001). The levels of GUSBP11 and miR-185-5p increased and decreased with the severity of CP, respectively (P < 0.01). LPS induces the decrease of HGF activity and the activation of inflammatory response, and the decrease of GUSBP11 may prevent the adverse effect of LPS on HGF (P < 0.001). Dual luciferase reporter genes showed that miR-185-5p interacts with GUSBP11. The increase of miR-185-5p also significantly improved the negative effect of LPS induction on HGF (P < 0.001).Conclusion: GUSBP11 promotes the inflammatory response and proliferation inhibition of human gingival fibroblasts induced by LPS by down-regulating miR-185-5p, thus promoting the development of CP. Keywords: chronic periodontitis, inflammation, GUSBP11, miR-185-5p